A Pilot Study on the Quality of Sexual Life of Patients Receiving Home Palliative Care in Poland - Marcin Janecki; Izabela Kaptacz; Zuzanna Janecka; Violetta Skrzypulec-Plinta (Sexes, 2021)
Background: Quality of life, physical, psychic, and social functioning assessments in patients suffering from chronic, progressive, and incurable diseases are one of the most significant aims of the palliative care home teams. Sexuality and intimacy can be one of the most important elements of a person’s life, even at the end of it. Unfortunately, there is very little interest in this topic among medical staff of palliative care units. The objective of the study: The aim of this study was to assess the health status, the quality of life, the quality of sexual life, and the recognition and resolution of sexual problems by the palliative care team in adult patients in the advanced stage of terminal illness, who were receiving home palliative care. Research methods: The study involved 342 adult patients in the advanced stage of incurable, progressive disease, covered by home palliative care in 15 facilities in Poland. A generic EuroQoL 5-Dimension 3-Level health and quality of life assessment questionnaire and a questionnaire developed by the researchers, including questions about sexual problems, were used in this prospective study. Results: The presented results are the part of the more extensive study. The assessment of health status and quality of life of the study patients showed that the evaluation was the lowest for performing ordinary daily activities. The quality of sexual life after diagnosis in more than half of the study patients has worsened. Almost half of the respondents felt that the palliative care team did not recognize or address their sexual concerns. Patients indicated nurses and physicians as the members of the palliative care team most helpful in identifying and addressing sexual concerns. Conclusions: Members of the palliative care team should receive training in communication with patients concerning their sexual life, their needs and expectations and have knowledge about options for obtaining specialized sexological care. It is necessary to prepare and validate simple tools that will facilitate the initiation of appropriate communication between patients and members of the medical staff. It will be important to conduct more detailed and targeted research on sexuality and intimacy in the Polish palliative care patient population.